Macroeconomic Implications of Aging in East Asia Pacific : Demography, Labor Markets and Productivity - Flochel, Thomas; Ikeda, Yuki; Moroz, Harry; Umapathi, Nithin (World Bank, Washington, DC, 2015)
This background paper was prepared for the East Asia Pacific aging report. The East Asia and Pacific region grew at an unparalleled rate in the past 50 years. This economic boom is partly attributable to unprecedented demographic changes in East Asia during this period. But demographics are only part of the story. The size of the economic bonus or burden which results from population aging depends on how policy influences labor force participation, savings, human capital accumulation and total factor productivity.